Pemanfaatan Limbah Buah Jeruk sebagai Bahan Pupuk Organik Cair - Gustine Devi Novita Saragih; Choirul Amri; Mohamad Mirza Fauzie (Sanitasi: Jurnal Kesehatan Lingkungan, 2020)
In Yogyakarta City, the most waste comes from markets and settlements. One market that produceshighest waste is Kranggan Market which produces 95% of organic waste, containing vegetablesand citrus fruit waste. The purpose of this study was to determine the effect of ingredientscomposition of citrus waste on the chemical content (N, P, K and pH) of organic liquid fertilizer.The study was a quasi experiment with post test only design. The study data was analysedusing one way anova at 0.05 significant level, and the results show that the N content obtainedp-value 0.961, the P content was 0.962, the K content was 0.948, and the pH was 0.702. The Ncontent had the highest average at 2 kg, i.e. 0.08%; meanwhile the K content was at 3 kg composition,0.05%; and pH was at 3 kg composition, 3.7. It can be concluded that the all compositionshave not meet the required minimum standards, meanwhile the P content has fulfilledSNI 19-7030-2004 with standard >0.10%, i.e. at 1 kg composition has an average of 0.10%, at 2kg composition, of 0.11%, and at 3 kg composition, of 0,11%. It can be concluded that the overallliquid organic fertilizer from citrus fruit waste have not meet the 2004 Standards. Therefore, itadvised for subsequent studies to add raw materials consists of vegetables or fruit which containhigh levels of nitrogen, phosphorus and potassium.